2004
DOI: 10.1177/0363546503259354
|View full text |Cite
|
Sign up to set email alerts
|

Humeral Torque in Professional Baseball Pitchers

Abstract: Fractures are most likely to occur near the time of maximum shoulder external rotation when humeral torque peaks. Pitchers whose elbows were more extended at stride foot contact tended to have lower peak humeral torques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 33 publications
5
107
1
2
Order By: Relevance
“…At the moment of transition from the late-arm-cocking to the early-arm-acceleration phases, external rotation torque occurs in the mid-to-distal humerus because the internal rotator muscles of the shoulder and the humerus initiate internal rotation of the proximal part of the humerus before the distal part. This external rotation torque causes a humeral fracture that is spiral in nature and located distal to the insertion point of the internal rotator muscle groups: the subscapularis, latissimus dorsi, and pectoralis major [5,13]. This type of fracture is seen mostly in recreational sports or in young athletes, and rarely seen in professional players [2,14], because they are more resistant to fractures owing to years of throwing motion that have produced adaptation by means of cortical hypertrophy and altered shoulder biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment of transition from the late-arm-cocking to the early-arm-acceleration phases, external rotation torque occurs in the mid-to-distal humerus because the internal rotator muscles of the shoulder and the humerus initiate internal rotation of the proximal part of the humerus before the distal part. This external rotation torque causes a humeral fracture that is spiral in nature and located distal to the insertion point of the internal rotator muscle groups: the subscapularis, latissimus dorsi, and pectoralis major [5,13]. This type of fracture is seen mostly in recreational sports or in young athletes, and rarely seen in professional players [2,14], because they are more resistant to fractures owing to years of throwing motion that have produced adaptation by means of cortical hypertrophy and altered shoulder biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al 6 used humeri with lengths ranging from 30 to 36 cm, and concluded that the high variability of bone quality among the specimens used caused the wide standard deviation of the test results, since their investigation included osteoporotic bones. Further, Sabick et al 7 concluded that the human peak humeral axial torque reached a mean value of 92 ± 16 Nm near the time of maximum shoulder external rotation at the end of the cocking phase in a throwing motion. Schopfer et al 8 used 17 human humeri with an mean age of 75 years (range: 53-92 years) and with humeri lengths ranging from 23.5 to 31.5 cm (mean 26.6 cm) and showed that intact bones have a mean torsional strength of 53.1 Nm (range: 20.9-100 Nm) and mean angular rotation at failure was 26.6°(range: 17.1-38.4°).…”
Section: Discussionmentioning
confidence: 99%
“…Non-weight bearing bones could also be susceptible to stress fractures depending on the activity. Baseball pitchers are at a higher risk of midshaft humeral stress fractures, as this site is loaded repetitively during throwing (23). Similarly, rowers and golfers are at a higher risk of stress fractures in the rib (24-26).…”
Section: Extrinsic Risk Factorsmentioning
confidence: 99%
“…Some investigators believe that muscles produce large strains in bone, especially at the muscle attachment points (29). This could potentially contribute to the occurrence of stress fractures in the upper body, such as at the ribs during rowing (25) and golfing (24), or in the humerus during throwing (23).…”
Section: Intrinsic Risk Factorsmentioning
confidence: 99%